Evaluation of Apoptotic Effects of Cell Wall and Cytoplasmic Extract from Saccharomyces cerevisiae on K562 Cell Line - F Bonyadi; V Nejati; A Tukmechi; SH Hasanzadeh; M Riki (Armaghane Danesh Bimonthly Journal, 2013)
Abstract Background & aim: Probiotics are living microorganisms that have beneficial effects, such as anti-tumor effects on the health. The aim of this study was to evaluate the inhibitory effect of cell wall and cytoplasmic extracts of Saccharomyces cerevisiae as a probiotic cancer Category K562 (myeloid leukemia) and apoptotic effects of this yeast. Methods: In this experimental study, the Saccharomyces cerevisiae was cultured, and using the micro sonicator the cell wall and cytoplasmic extracts were separated. Then, different concentrations of cell wall and cytoplasmic extracts were prepared. The inhibitory growth percentage of cancer K562 cell line at different times (12, 24, 48 and 72 h) was measured by MTT assay. Apoptosis and necrosis were also evaluated by DNA fragmentation electrophoresis method. The collected dara were analyzed by ANOVA and Tukey test.